Chemosensory dysfunction, Oral disorders and Oral health-related quality of life in patients with primary Sjögren's syndrome: comparative cross-sectional study - Mirjana Šijan Gobeljić; Vera Milić; Nada Pejnović; Nemanja Damjanov (BMC, 2020)
Abstract Background The aim of this study was to evaluate chemosensory function and oral disorders in patients with primary Sjögren's syndrome (pSS) and to compare these findings with those of age- and gender-matched healthy controls. Methods This comparative cross-sectional study included 58 patients with primary Sjögren's syndrome (pSS) and 55 age- and gender-matched healthy controls. Olfactory and gustatory function, burning sensations in the tongue (BST) and halitosis were assessed. Oral health-related quality of life (OHRQoL) was evaluated using the short-form Oral Health Impact Profile (OHIP-14). Results Patients with pSS had significantly lower self-reported visual analogue scale (VAS) smell score (8.6 ± 2.2 vs. 9.6 ± 0.7, p = 0.016) and VAS taste score (8.5 ± 2.1 vs. 9.5 ± 0.7, p = 0.014) than healthy controls. A greater proportion of patients with pSS had anosmia (3.8% vs. 0.0%) or hyposmia (36.5% vs. 13.2%) and ageusia for basic tastes: sweetness (34.0% vs. 7.5%), sourness (10.6% vs. 0.0), saltiness (10.0% vs. 5.7%) or bitterness (19.1% vs. 1.9%) as evaluated using Sniffin Sticks test and taste stripts, respectively. A higher proportion of pSS patients complained of dysgeusia (52.6% vs. 9.4%, p < 0.0001) and BST (45.6% vs. 0.0%, p < 0.0001), while similar number of patients with pSS and controls reported halitosis (31.6% vs. 28.3%, p = 0.434). The mean OHIP-14 score was significantly higher in patients with pSS (6.8 ± 7.0 vs. 2.3 ± 8.5, p < 0.001) indicating patients' poorer OHRQoL compared with controls. Conclusions The majority of patients with pSS had impaired chemosensory function and indicators of oral health in comparison with the age- and gender-matched healthy controls. Further studies of oral hygiene habits and dietary intake of these patients are needed to ensure better management of oral health problems in patients with pSS.